Summer diet of the pichi Zaedyus pichiy (Xenarthra: Dasypodidae) in Mendoza Province, Argentina - Superina, Mariella (2009)
The diet of the pichi armadillo (Zaedyus pichiy) was determined based on analysis of stomach contents of 26 dead individuals confiscated from poachers near Cerro Nevado, Mendoza Province, Argentina. Sand accounted for 66 ± 24% of stomach contents' dry weight. Beetles were the predominant food item in 14 and ants in 5 stomachs, while 5 animals had mainly ingested plant material. The remainder had mostly fed on fly larvae and arachnids. Coleoptera (mainly adults and Scarabeidae larvae) and plant material (seeds, leaves, and roots) were found in all stomachs examined. All pichis had fed on ants of different species and stages, suggesting that pichis eat any ant species they can find and actively prey on nests. Scorpions and spiders were observed in over 60% of stomachs but represented a low aggregate percent weight. Vertebrates were rarely found. Based on these results, the pichi of Mendoza Province can be described as an opportunistic omnivore that mainly feeds on insects and seems to be the least carnivorous of all carnivore-omnivore armadillos.